CAPABILITY OF LOCAL GOVERNMENT IN THE MANAGEMENT PUBLIC MARKET SIMPANG BARU IN DISTRICT TAMPAN OF PEKANBARU CITY IN 2017 - Isnaini "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Public Market Simpang Baru is one of the public markets managed by the Pekanbaru City Government through the Pekanbaru City Market Service. To maintain the existence of the people's market, regulation and revitalization required by building the facilities and infrastructure needed to improve the image of the people's market which is clean, safe, comfortable, efficient and competitive. To support the management of the public market, Pekanbaru City Government stipulates Regional Regulation Number 09 of 2014 concerning Management of the Public Market, Shopping Centers and Supermarkets. So with this the local government through the Pasar Simpang Baru UPTD has a responsibility in managing the Simpang Baru public Market.This study aims to describe the Local Government Capability in Managing the Simpang Baru Public Market in the Handsome District of Pekanbaru City in 2017. The location of this study was conducted at the Simpang Baru Public Market in Tampan District. Data collection techniques are carried out by interviews and documentation. The method used in this research is qualitative descriptive.The results of this study indicate that the capability of the Simpang Baru Market UPTD in managing the Simpang Baru Public Market has not gone well. This can be seen from the manager of the Simpang Baru Public Market which has not been clearly managed because in the Simpang Baru People's Market there are two managers namely the Simpang Baru Market UPTD and the private community, then the Simpang Baru Market's human resource capacity is not sufficient to help manage Simpang Baru People's Market , Finance that is inadequate in supporting the management of the Simpang Baru Public Market, because the collection of market retribution has not been maximized and the lack of supervision carried out by the Pekanbaru City Market Service and the Simpang Baru Market UPTD towards the Simpang Baru Public Market.Keywords: Capability, Management, Public Market